Phospholipidase Dδ Negatively Regulates the Function of Resistance to Pseudomonas syringae pv. Maculicola 1 (RPM1) - Yuan, Xin; Wang, Zhangying; Huang, Jianzhong; Xuan, Hua; Gao, Zhiyong (Frontiers in Plant Science, 2019)
RPM1 is a plant immune receptor that specially recognizes pathogen-released effectors to activate effector-triggered immunity (ETI) in Arabidopsis thaliana. RPM1-mediated ETI results in the hypersensitive response (HR) and the disease resistance. Previous reports indicated that Phospholipase D (PLD) positively regulated RPM1-mediated HR. However, single, double, and triple pld knock-out mutants of 12 members of the PLD family in A. thaliana did not show suppressed RPM1-mediated HR, indicating the functional redundancy among PLD members. In this study, we revealed that PLD could negatively regulate the function of RPM1. We found that RPM1 had protein-protein interactions with PLDα2 and PLDδ, but did not interact with PLDβ1, PLDβ2, and PLDγ3. Overexpression of PLDδ was able to reduce the protein level of RPM1, and the functions of RPM1 were consequently deficient in the PLDδ overexpression plants. We treated the leaves of A. thaliana with abscisic acid (ABA) to stimulate internal PLD activity, and found that the protein level of RPM1 reduced at 3 hours after treatment. ABA-induced RPM1 reduction was suppressed by n-butanol, the antagonist of PLD activity, suggesting that PLD activity and PLD-derived phosphatidic acid (PA) were required for ABA-induced RPM1 reduction. Therefore, PLD is not only a positive signal transduction component for activated RPM1, but also negatively regulates the protein level of the prosignaling inactive RPM1 to restrict the initial signaling output of RPM1. Because different environmental and physiological stimuli can induce PLD activity, and PLD activity plays both negative and positive roles for RPM1 function, our study indicates that PLD proteins are regulating points to integrate the abiotic and biotic responses of plants.